CONTRAST BATH SOAKING THERAPY IMPROVES BLOOD CIRCULATION IN DIABETIC FEET - Berkah Afif Udin; Umi Faridah; Muhamad Jauhar; Faridha Alfiatur Rohmaniah ((IJP) Indonesia Jurnal Perawat, 2025)
AbstractDiabetes Mellitus (DM) is the mother of all diseases that can "give birth" to various other diseases. DM patients are at risk of diabetic ulcers due to poor blood circulation in the feet. The prevalence of diabetic neuropathy is high in DM patients. The most important DM management program is to normalize blood glucose levels. The study aims to analyze the effect of contrast bath immersion on blood circulation in the diabetic feet. This study uses a quasi-experimental research design using a nonequivalent control group design. The independent variable is contrast bath therapy, and the dependent variable is leg blood circulation. The research was conducted at a private Islamic hospital in Banjarnegara Regency in February 2025. The sample was 18 DM clients for each group determined using a purposive sampling technique according to certain criteria. The instrument used a GEA stethoscope type SF 411 and a GEA MC 20 sphygmomanometer. The intervention group received contrast bath therapy by soaking their feet for 2 minutes in warm water and 1 minute in cold water. Therapy is given 5 times in 15 minutes and 3 days. The control group received standard intervention through 30-degree leg elevation. Data analysis used the Wilcoxon and Mann-Whitney tests. The results showed that contrast bath immersion therapy increased blood circulation in the legs with a value of p=0.001 (p0.05). Hospitals need to develop an SOP for contrast bath therapy and apply it to DM clients as an independent nursing intervention that can improve leg’s blood circulation.